Initial studies on in vitro germination and early seedling growth of Nepenthes truncata MACF - Maquilan, Mary Ann D. (2003)
A protocol for in vitro seed germination of the endangered Philippine pitcher plant, Nepenthes truncate, was developed from a series of seed sterilization trials and germination experiments involving three factors: seed pretreatments, culture medium and salt concentration. Germination studies were done in independent but simultaneous experiments using flasks and jars. Highest efficiency of seed sterilization (90.8%) was obtained by a combination of 70% isopropyl alcohol, 10% commercial bleach, and 3%hydrogen peroxide. This procedure resulted in 83.7% germination based on a sample size of 520 cultures. Germination in in vitro culture was achieved in 18 to 74 days. A previous study reported germination time of 28 to 180 days. Soaking in sugar solution could increase the initial germination percentage. The treatment that gave the highest final germination percentage was a combination of seed hardening and Murashige and Skoog (92.4%) or Knudson C medium (92.2%). Flasks capped with paper and aluminum sheets produced healthier seedlings than jars with unvented metal caps. Knudson C gave superior effects on seedlings that eventually became chlorotic of necrotic and were not able to supervise longer in cultures. Abnormalities were most severe in seedlings exposed to three-fourth to full concentration of MS salts.
Thesis (BS Biology) -- University of the Philippines Mindanao, 2003